Waking up married - Ryan, Reese (Ryan, Reese . Bourbon brothers., 2021)
"Their night on the town is a blank, but when Zora Abbott and Dallas Hamilton awaken in a Vegas hotel room, they're man and wife. With news of the nuptials spreading virally, the high-profile best friends decide to stay married, temporarily. Maybe under the cover of marriage, Dallas can even make his best friend's baby dream come true. But can their friendship survive their newly unleashed passions?"--Back cover.